2004
DOI: 10.1111/j.1365-2826.2004.01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of p53 mRNA in the Brain and Pituitary During Repeated Immobilization Stress: Negative Correlation with Glucocorticoid Receptor mRNA Levels

Abstract: In our previous study, apparent reduction of glucocorticoid receptor (GR) mRNA was seen in the hippocampus and the hypothalamic paraventricular nucleus (PVN) during repeated immobilization (IMO) stress, but not following starvation. Our laboratory has also shown that the sp1 activates, whereas tumour suppressor p53 represses the promoter activity of GR gene. In an attempt to reveal the possibility that transcription factors such as sp1 and/or p53 are involved in the regulation of GR mRNA expression in the hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 51 publications
2
19
0
2
Order By: Relevance
“…It has previously been reported that unstressed prepubertal and adult males have similar levels of hippocampal GR mRNA [36], and the present results support these findings. In addition, our data indicate that prepubertal animals also exhibit a similar decrease in hippocampal GR expression in response to acute stress in both dorsal and ventral hippocampus, as has been previously reported for adults [12,13,14,15,16]. Unlike the reported down-regulation of GR typically observed in response to acute stress, chronic stress does not commonly alter GR expression in adults [37].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It has previously been reported that unstressed prepubertal and adult males have similar levels of hippocampal GR mRNA [36], and the present results support these findings. In addition, our data indicate that prepubertal animals also exhibit a similar decrease in hippocampal GR expression in response to acute stress in both dorsal and ventral hippocampus, as has been previously reported for adults [12,13,14,15,16]. Unlike the reported down-regulation of GR typically observed in response to acute stress, chronic stress does not commonly alter GR expression in adults [37].…”
Section: Discussionsupporting
confidence: 56%
“…In adults, hippocampal GR expression is generally decreased in response to stress [12,13,14,15,16]. However, it is presently unknown whether acute or chronic stress may differentially affect GR levels in the hippocampal formation of prepubertal compared to adult animals.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest to the current study are reports demonstrating that a 3-day restraint stress paradigm decreased Bcl-2 immunoreactivity in the hippocampus, whereas poststress 1-or 3-week olanzapine treatment reversed the decrease in the intensity of Bcl-2 staining to pre-stress levels; Bcl-xl and Bax were not examined (Luo et al, 2004). In other reports, repeated immobilization stress increased mRNA expression of the tumor suppressor gene p53 in hippocampal subfields (Nishimura et al, 2004) and decreased Bcl-2 mRNA expression in the hippocampus (Yun et al, 2003). Increased Bcl-2 immunoreactivity in the hippocampus has also been observed following chronic treatment with the antidepressants, amitriptyline and venlafaxine (Xu et al, 2003).…”
Section: Introductionmentioning
confidence: 68%
“…Subsequent works to elucidate the effect of stress on GR expression have been unable to identify a common effect of stress on GR expression in the hippocampus. Conflicting studies have shown GR mRNA levels to remain stable [10,11,12,13,14] or decrease [10,15,16] after a variety of stressors including forced swimming, restraint, Morris water maze exposure, and novelty stress. Thus far, stress-induced GR mRNA expression has generally been measured by either polymerase chain reaction (PCR) analysis of whole hippocampi [10,13] or via in situ hybridisation [11,12,14,15].…”
Section: Introductionmentioning
confidence: 99%